Black rice (Oryza sativa L.) and its anthocyanins: mechanisms, food applications, and clinical insights for postprandial glycemic and lipid regulation - Thavaree Thilavech; Tanyawan Suantawee; Charoonsri Chusak; Phim On Suklaew; Sirichai Adisakwattana (Food Production, Processing and Nutrition)
Abstract Postprandial hyperglycemia and hyperlipidemia are key contributors to chronic metabolic disturbances, thereby promoting the onset and progression of cardiovascular diseases and diabetes. Current dietary interventions aim to effectively control postprandial glucose and lipid levels while ensuring adequate antioxidant intake. Black rice (Oryza sativa L.) cultivations have gained attention for their resistant starch content and phytochemical compositions. Notably, black rice is rich in anthocyanins, known for their anti-diabetic and antioxidant effects. This review demonstrates the potential of black rice in regulating postprandial glycemic and lipid responses, thus extending its applications to the development of functional food products. Based on in vitro studies, black rice anthocyanins exhibit a variety of mechanisms, including the inhibition of carbohydrate and fat digestive enzymes, binding to bile acids, interference with cholesterol micellization, and the inhibition of glucose and cholesterol uptake in enterocytes. Utilizing black rice flour and its anthocyanin-rich extracts in food products enhances health benefits by suppressing starch digestibility and increasing phytochemical content and antioxidant capacity. Clinical studies support the potential of black rice and its food derivatives to effectively manage postprandial glycemic and lipidemic responses while increasing plasma antioxidant capacity. However, comprehensive, long-term investigations are crucial to delineate the optimal dosage and duration of black rice consumption and further elucidate its positive effects on metabolic responses. Graphical Abstract